ON THE QUESTION OF THE METHODOLOGY OF PSYCHOLOGICAL ANALYSIS OF VISUAL ART (Psychology Travelogs, 2025)
The article discusses the peculiarities of artistic creativity that pose significant problems for the psychological study of art in general and visual arts in particular. The reasons for the ineffectiveness of existing methods of psychological research in art are identified, which are due to the significant role of subjective and unconscious components of artistic creativity, the complexity of experimental research and modelling of the artistic process, and the vagueness of criteria for evaluating works of art. Additional difficulties are added by the special effect of the researcher's detachment from the practical process of creation, which complicates the process of understanding art. All this often makes quantitative research methods commonly accepted for the analysis of scientific creativity ineffective in the field of studying artistic creativity and raises the question of more relevant approaches to this problem.The article analyses the possibilities of overcoming these difficulties on the basis of successful examples of in-depth scientific approaches to the study of the artistic process and the analysis of works of art with the definition of the basic principles of artistic creativity. Ways of applying a more effective methodology of psychological research are identified.It concludes that new methods of psychological research need to be introduced in visual arts, including in-depth analysis of the fundamental principles of the artistic process, the use of interdisciplinary approaches, empathy, psychological analysis of visual elements present in the finished work, and consideration of the specific features of creativity in this field.
Keywords: psychology of artistic creativity; methodological problems of art research; effective methods of psychological research in the visual arts